Specific features of composition, age and a model of formation of gabbroids of the Andean complex (Cape Tuxen, Western Antarctica) - D. P. Gladkochub; T. V. Donskaya; V. G. Bakhmutov (Ukrainian Antarctic Journal, 2012)
The detail geological, petrological and geochronological studies of Andean intrusive rocks near the UAS Akademik Vernadsky which are represented by amphibole and olivine gabbros were carried out. For most of them the lithospheric subduction source are clearly defined. But for the some samples (gabbrodiorite) the mixed (heterogeneous) source which is formed by mixing of asthenospheric and undepleted subduction components. The last one may be due to breaking of the lithospheric plates under extension of the continental lithosphere and infiltration the asthenospheric mantle material into the upper levels.  These conditions correspond to the processes of destruction (collapse) of active continental margins.